Mathematics of investment - Abao, ZenonR; Marribay, Jose B. jt., au. (Mandaluyong City: Books Atbp. Publishing Corporation, 2014)
Simple interest --Compound Interest --Mathematics of Annuities --Annuities: General Case --Amortization and sinking fund --Bonds --Mathematics of Depreciation.
Chapter 1.--Simple interest --2. Compound interest --3. Mathematics of annuities --4. Annuities: General case --5. Amortization and sinking fund --6. Bonds --7.Mathematics of depreciation.
Includes Index of tables; Bibliography
Keywords: Mathematics; Business mathematics; Mathematics -- Investments